Management of Endometriomas Prior to IVF. Issue 3 (July 2017) - Maiorana, Antonio; Incandela, Domenico; Mercurio, Antonella; Alio, Walter; Giambanco, Laura; Alio, Luigi
Endometriosis causes a decrease in fertility in affected patients. The different forms of the disease, peritoneal, ovarian, deep infiltrating and adenomyosis, are often present in varying degrees in the same patient, either together or individually, and cause infertility through a pathogenesis that is not yet clear. A significant number of women with endometriosis and endometriomas will eventually seek assisted reproductive technology (ART) for conception. The specific impact of endometriomas alone and the impact of surgical intervention for endometriomas on the reproductive outcome of women undergoing in vitro fertilization/intra-cytoplasmic sperm injection (IVF/ICSI) are areas that need further clarification and, for this reason, the management of endometriomas before clinical IVF is a very complex topic. In order to provide useful information for the clinical management of patients with endometriomas having IVF, in this review we investigated: the impact of the presence of endometriomas, both individually and associated with other types of the disease, on IVF techniques; the possible role of surgery and its possible negative effects; the risks and difficulties related to conservative management during IVF procedures.